Effect of Participatory Learning and Action Malaria to Decrease the Number of Occurrence Malaria in Pregnant Women in Hiri Island District in Ternate City - Hetty Astri; Farida Alhadar (ICETIA, 2016)
This study aims to identify the influence ofParticipatory Learning and Action (PLA) against the numberof Malaria disease cases in pregnant women in district of HiriIsland, Ternate City. This research uses qualitative research ofphenomenology approach. The data is obtained byinterviewing of informants, and then analyzed by usingthematic analysis.Results show that the public participation in combating thespread of malaria mosquitoes by cleaning and hoardingpuddles and other sources can reduce the spread of diseasecases of malaria in pregnant women in District of Hiri Island,where in previously, there were 18 people and decreased by 5people.